Pt/Ga-SBA-15 composites synthesis and characterization (Superficies y Vacío, 2020)
Pt (0.5, 1 and 1.5 wt%) was impregnated by incipient wetness on SBA-15 and corresponding  Ga-modified (3, 5, 10 and 20 wt%) composites. Gallium nitrate was incorporated directly during the mesoporous siliceous network synthesis. Materials were characterized by N2 physisorption, X-ray diffraction, Fourier transformed infrared spectroscopy, scanning electron microscopy and transmission electron microscopy. SBA-15 had surface area greater than 800 m²/g that decreased by Ga incorporation in binary materials. It seemed that tetrahedral gallium was well-incorporated into mesoporous silica walls. Pt dispersion slightly diminished (as to that on SBA-15) by augmenting Ga concentration in composites. Corresponding pore size maxima shifted to lower diameters (as to that of non-impregnated supports) after platinum loading suggesting Pt crystals inside pores of SBA-15 and Ga-modified carriers. Large cubic platinum crystals were observed over all prepared materials probably due to sintering (during calcining at 500 °C) of metallic particles weakly interacting with the carriers surface. After materials annealing (500 °C under static air) metallic platinum was evidenced (by XRD) pointing out to noble metal reduction that could be facilitated by decomposition of organic remains from Si alkoxide used during supports synthesis which presence was ascertained by FTIR.